2019
DOI: 10.1007/s13197-019-03842-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canola proteins on rice flour bread and mathematical modelling of the baking process

Abstract: The aim of the present work was to study the technological impact of incorporating canola protein concentrate (extract) into gluten-free bread formulation made of white rice flour. The main properties of the obtained dough and bread were compared to two control formulations made of 100% wheat flour and 100% rice flour. The canola protein concentrate was added at 3, 6 and 9% supplementation level of the rice flour. The bread making process was conducted by approved technology and the obtained results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…The mean cohesiveness values increased during storage, but these changes were not significant relative to the control sample. The cohesiveness of the sunflower cake-enriched products (regardless of the additive dose) did not differ significantly in the bread samples stored for 48 h. Similar trends in changes in chewiness and cohesiveness were reported by Salah et al 38 . The authors enriched bread with gluten-free rapeseed protein, and the products were characterized by lower hardness and chewiness, with a slight increase in cohesiveness and springiness.…”
Section: Discussionsupporting
confidence: 85%
“…The mean cohesiveness values increased during storage, but these changes were not significant relative to the control sample. The cohesiveness of the sunflower cake-enriched products (regardless of the additive dose) did not differ significantly in the bread samples stored for 48 h. Similar trends in changes in chewiness and cohesiveness were reported by Salah et al 38 . The authors enriched bread with gluten-free rapeseed protein, and the products were characterized by lower hardness and chewiness, with a slight increase in cohesiveness and springiness.…”
Section: Discussionsupporting
confidence: 85%
“…Levels of addition higher than 9% resulted in higher bread volume and lower hardness of the breads during storage compared to control bread. In another study, when canola proteins were added to a white rice flour bread recipe up to 6% resulted in an improvement of the technological properties of the dough and the resulted bread [ 25 ].…”
Section: Plant-based Gluten-free Proteinmentioning
confidence: 99%
“…Accordingly, our results indicate that adding high levels of Longdao 19 rice flour may improve the structure and quality of gluten networks in dough. Studies have found that the protein network is always related to the strength of flours, and it usually depends on the higher farinograph stability (Shin et al ., 2018; Salah et al ., 2019; Xu et al ., 2019). Thus, compared with the control dough, the addition of Longdao 19 rice flour may have a positive effect on the farinograph properties of dough, and then may improve the quality of the mixed flour dough.…”
Section: Resultsmentioning
confidence: 99%